Youth purpose through the lens of the Theory of Organizing Models of Thinking. Issue 3 (3rd July 2017) - Arantes, Valeria; Araujo, Ulisses; Pinheiro, Viviane; Moreno Marimon, Montserrat; Sastre, Genoveva
Abstract: Purpose represents a unique opportunity for identifying and analyzing the complexity of human reasoning, considering that its constitution brings together cognitive, affective and social elements. In this article, we use the Theory of Organizing Models of Thinking (OMT), an epistemological and methodological approach based on developmental psychologist Jean Piaget's work, to present a different perspective on how to analyze youth purpose and to explain the cognitive-emotional dynamics of reasoning in everyday thinking. We introduce OMT and its benefits, then explore the insights it can provide through examining seven OMTs used by Brazilian youth about their life purposes. These models focus on: consumerism and financial stability, interpersonal relationships, only work, work and family, idealization of work and family, altruistic intentions, and fragile purpose projections. These models show how reasoning and emotion are complexly linked in everyday thinking.